Separation and men's violence against women - Ekbrand, Hans (University of Gothenburg, 2007)
Separations and men's violence against women is a study that aims to increase knowledge about the connection between men's violence against women and separations. The study is a thesis at the University of Gothenburg and has been carried out with financial support from the Crime Victims Fund. The study is based on questionnaires collected from over 350 women who have separated or gone through a divorce from a heterosexual relationship. In order to get in touch with these women, the researcher has worked together with various social agencies that women who have been subjected to separation violence can come into contact with; police, women's shelters, crime victim shelters, social services and family law agencies. Questionnaires have also been sent directly to women in the Gothenburg area who have gone through a divorce.

The study includes two questionnaires. Questionnaire 2 was sent after 6 months to those women who expressed interest in participating further via Questionnaire 1. The questionnaires are designed to cover different periods of the relationship and separation. They include questions about the man's behavior in certain situations, for example during discussions about joint children or assets, how conflicts have been handled, physical, psychological and sexual violence and the relationship as a whole.

The results of the study show that 60 percent of the women respondents have at some point been subjected to physical violence by the man they separated from. One purpose of the study is to investigate whether it is possible to predict the risk of violence after a separation. The study shows that the risk assessment model, to assess how great the risk is that the woman will be subjected to violence even after the separation, which is used by staff at women's shelters and crime victim shelters, is preferable to the police's way of working. It also shows that negotiations in family law are affected if the man has used violence. It often turns out that the woman lowers her demands, for example regarding custody of joint children, if the man has used violence against her.

Purpose:
To investigate the extent of men's violence against women in connection with and after separations, separation violence, in order to be able to say something about the risk of violence that women who are considering leaving a heterosexual relationship face.

Separationer och mäns våld mot kvinnor är en studie som syftar till att öka kunskapen om sambandet mellan mäns våld mot kvinnor och separationer. Studien är en avhandling vid Göteborgs universitet och har genomförts med ekonomiskt stöd från Brottsofferfonden. Undersökningen bygger på insamlade enkäter från drygt 350 kvinnor som har separerat eller genomgått en skilsmässa från ett heterosexuellt förhållande. För att komma i kontakt med dessa kvinnor har forskaren arbetat tillsammans med olika samhälleliga instanser som kvinnor som utsatts för separationsvåld kan komma i kontakt med; polis, kvinnojourer, brottsofferjourer, socialkontor och familjerättsbyråer. Enkäter har även skickats direkt till de kvinnor i göteborgsområdet som genomgått en skilsmässa.

Studien omfattar två enkäter. Enkät 2 skickades efter 6 månader till de kvinnor som via Enkät 1 meddelat intresse för att delta ytterligare. Enkäterna är utformade för att täcka in olika perioder av förhållandet och separationen. De innehåller bland annat frågor om mannens beteende vid vissa situationer, exempelvis under diskussioner om gemensamma barn eller tillgångar, hur konflikter har hanterats, fysiskt, psykiskt och sexuellt våld och förhållandet i helhet.

Resultatet av studien visar att 60 procent av de svarande kvinnorna har någon gång utsatts för fysiskt våld av den man de separerat ifrån. Ett syfte för studien är att undersöka huruvida det går att förutsäga risken för våldsanvändning efter en separation. Studien visar att den riskbedömningsmodell, för att bedöma hur stor risken är att kvinnan utsätts för våld även efter separationen, som används av personal på kvinnojourer och brottsofferjourer är att föredra gentemot polisens arbetssätt. Även att förhandlingar i familjerätten påverkas om mannen använt våld. Ofta visar det sig att kvinnan sänker sina krav, vad gäller exempelvis vårdnaden om gemensamma barn, om mannen använt våld mot henne.

Syfte:
Att utreda omfattningen av mäns våld mot kvinnor i samband med och efter separationer, separationsvåld, för att därigenom kunna säga något om den risk för våld som kvinnor som överväger att lämna ett heterosexuellt parförhållande står inför.
Separationer och mäns våld mot kvinnor
Keywords: DOMESTIC VIOLENCE; FAMILJERELATERAT VÅLD; CHILDREN; BARN; DIVORCE; SKILSMÄSSA; FAMILY LAW; FAMILJERÄTT; WITNESS INTIMIDATION; VITTNESHOT; CORPORATE OWNERSHIP; BOLAGSÄGANDE; CHILD SUPPORT PAYMENTS; UNDERHÅLLSBIDRAG TILL BARN; DOMESTIC SAFETY; SÄKERHET I HEMMET; SEXUAL OFFENCES; SEXUALBROTT; SEXUAL ASSAULT; VÅLDTÄKT; WOMEN; KVINNOR; MARRIED WOMEN; GIFTA KVINNOR; MARRIED MEN; GIFTA MÄN; MEN; MÄN; DIVORCED; SKILD; SEPARATED; SEPARERAD; PERSONAL SAFETY; PERSONLIG TRYGGHET; ASSAULT; VÅLD; Crime and law enforcement; Kriminalitet och rättstillämpning; Family life and marriage; Familjeliv och äktenskap; Social Sciences; Samhällsvetenskap; Sociology; Sociologi